Macroeconomic indicators and corporate financial ratios in predicting financial distress - Dian Oktarina (The Indonesian Accounting Review, 2017)
In 2015, the performance of the textile and garment industry declined by 4.79% due to the global economic crisis which caused the textile and garment industry to experience a continuous deficit. This is a sign that the company is experiencing financial distress. Such a condition could have been recognized early if the financial statements and macroeconomic conditions had been carefully analyzed. The purpose of this study is to determine the macroeconomic indicators and financial ratios of companies in predict-ing financial distress. Data sampling in this research was taken from textile and gar-ment industry sector companies listed on the Indonesian Stock Exchange (IDX). Ma-croeconomic indicators used are lending rate, consumer price index, IDX Composite, inflation, and IDR/USD exchange rate. The financial ratios used are debt equity ratio, total asset turnover ratio, current ratio, quick ratio, working capital ratio, net income to total assets ratio, and cash ratio. This research uses logistic regression analysis. The results indicate that current ratio and quick ratio can be used to predict financial dis-tress. The next research can use other sector companies or all sector companies listed on the Indonesia Stock Exchange (IDX).